Feminism in A Room with A View Novel: Critical Analysis - Rahma Yunita Putri; Anisha Bunga Armethia Fitriane; Rizki Aji Saputro; Aldy Maulitta (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2022)
Feminist play with a range of choice in the process self-presentation, registering a relation both to the body and to the social meaning of womenhood. The main focus of this research is comparing and measuring the feminist issues by reading the novel